Strategy and steering in governance: The changing fates of the Argentine Planning Council - Alves Rolo, Rodrigo Hernán; Van Assche, Kristof; Duineveld, Martijn (Cogitatio Press, 2025)
Based on a detailed study of the return of national‐level planning in Argentina as embodied by COFEPLAN, the national planning council, we develop a conceptual framework to analyse the possibilities and limits of steering in governance. We lean on the theoretical apparatus of evolutionary governance theory and use the concepts of goal dependency, inter‐dependency, path dependency and material dependency (effects in governance) to analyse the reality effects of strategy (effects of governance). Methodologically, our study relies on archival work and semi‐structured interviews with planning scholars and public officials from different levels of government. We show that, although material and discursive reality effects were abundant in the evolution of Argentine planning policies, dependencies and discontinuities undermined both the central steering ambitions of the government and the innovative potential of the new planning schemes. The dramatic history of the Argentine planning system allows us to grasp the nature of dependencies in a new way. Shocks in general undermine long‐term perspectives and higher‐level planning, but they can also create windows of opportunity. The internal complexity and the persistence of Peronist ideology in Argentina can account for the revivals of national‐level planning in very different ideological contexts, but the recurring shocks, the stubborn difference between rhetoric and reality, the reliance on informality, created a landscape of fragmented governance and often weak institutional capacity. In that land‐ scape, steering through national‐level planning becomes a tall order.